Numerical Simulation of a Hybrid Nanocomposite Containing Ca-CO3 and Short Glass Fibers Subjected to Tensile Loading - Minoo Dokht Shokrian; Karim Shelesh-Nezhad; Behzad H Soudmand (Mechanics of Advanced Composite Structures)
The tensile properties of multiscale, hybrid, thermoplastic-based nanocomposites reinforced with nano-CaCO3 particles and micro–short glass fibers (SGF) were predicted by a two-step, three-dimensionalmodel using ANSYS finite element (FE) software. Cylindrical and cuboid representative volume elements were generated to obtain the effective behavior of the multiscale hybrid composites. In the first step, the mechanical performance of co-polypropylene/CaCO3 nanocomposite was analyzed. The thickness of the interphase layer around the nanoparticles was estimated by using differential scanning calorimetry data. In the second step, the nanocomposite (co-polypropylene/CaCO3) was considered as an effective matrix, and then the effect of micro-SGF inclusion on the corresponding effective matrix was evaluated. The FE and experimental stress-strain curves of multiscale, hybrid composites were compared at different weight fractions of the nanoparticle. The proposed two-step method can easily predict the tensile properties of multiscale, hybrid, thermoplastic-based nanocomposites.